ANALYSING THE IMPACT OF ADJUSTED NET SAVINGS ON TRANSNATIONAL INVESTMENT: A COMPARATIVE ANALYSIS OF THE USA AND THE PRC - Варакін, Артем; Руденко-Сударєва, Людмила; Шевченко, Юлія (Modern engineering and innovative technologies, 2024)
In the context of the simultaneous development of globalization and de-globalization processes of a turbulent environment that constantly catalyses changes in the directions and volumes of international investment by TNCs, there is a need to monitor the